2010
DOI: 10.1152/ajpgi.00330.2010
|View full text |Cite
|
Sign up to set email alerts
|

Combination of starvation interval and food volume determines the phase of liver circadian rhythm in Per2::Luc knock-in mice under two meals per day feeding

Abstract: Although the circadian liver clock is entrained by the feeding cycle, factors such as food volume and starvation interval are poorly understood. Per2::Luc knock-in mice were given two meals per day with different food volume sizes and/or with different intervals of starvation between two mealtimes with the total food volume per day fixed at 3.6 g (80 food pellets, ∼75% of free feeding) per mouse. The bioluminescence rhythm in the liver produced a unimodal peak but not bimodal peak under the regimen of two meal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 39 publications
(55 reference statements)
5
61
0
Order By: Relevance
“…It seems that food entrainment is dependent on the metabolic status and fasting period previous to the food signal (Escobar et al, 2007;Hirao et al, 2010;Mendoza et al, 2008b;Silver et al, 2011), and that an interaction with the LD cycle also exists (Froy et al, 2009;Silver et al, 2011). This could explain why the expression of a clock gene shows rhythmicity sometimes ( gPer1a in 24L group), but not always ( gPer1a in 24D, RnF and SF10-22 groups), even though all animals were randomly fed and without any photoperiodic signal.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that food entrainment is dependent on the metabolic status and fasting period previous to the food signal (Escobar et al, 2007;Hirao et al, 2010;Mendoza et al, 2008b;Silver et al, 2011), and that an interaction with the LD cycle also exists (Froy et al, 2009;Silver et al, 2011). This could explain why the expression of a clock gene shows rhythmicity sometimes ( gPer1a in 24L group), but not always ( gPer1a in 24D, RnF and SF10-22 groups), even though all animals were randomly fed and without any photoperiodic signal.…”
Section: Discussionmentioning
confidence: 99%
“…Our group reported that food volume and starvation intervals are important factors for determining the peripheral clock phase (141,142). A feeding schedule of 2 meals per day in mice induced only one peak in the rhythm of clock gene expression in peripheral tissues (141,143). On the other hand, a feeding schedule of 2 -3 meals per day in mice, with food intake following a longer fasting interval, was more effective at entraining the peripheral clock phase than other feeding schedules.…”
Section: Food Timingmentioning
confidence: 97%
“…Latenight dinners may cause changes in clock gene expression in the peripheral tissues. Our group reported that food volume and starvation intervals are important factors for determining the peripheral clock phase (141,142). A feeding schedule of 2 meals per day in mice induced only one peak in the rhythm of clock gene expression in peripheral tissues (141,143).…”
Section: Food Timingmentioning
confidence: 99%
“…Specific primer pairs were designed using Primer3 Input (version 0.4.0, [27]) on the basis of the published databases of Gapdh, Il-13, and Tnf-a genes: Gapdh, 5′-TGGTGAAGGTCGGTGTGAAC-3′ (forward) and 5′-AATGAAGGGGTCGTTGATGG-3′ (reverse); Il-13, 5′-ATGGCCTCTGTAACCGCAAG-3′ (forward) and 5′-GGCGAAACAGTTGCTTTGTG-3′ (reverse); and Tnf-a, 5′-ATCCGCGACGTGGAACTG-3′ (forward) and 5′-ACCGCCTGGAGTTCTGGAA-3′ (reverse). RT-PCR was performed under the following conditions, which were the same as described previously [28]: cDNA syn-thesis at 42˚C for 15 min followed by 95˚C for 2 min, PCR amplification for 40 cycles with denaturation at 95˚C for 5 s, and annealing and extension at 60˚C for 20 s. Gene amplification specificity was confirmed by measuring the size and purity of the PCR product by gel electrophoresis. The relative light unit of the PCR product of the target gene was normalized to that of Gapdh.…”
Section: Rna Isolation and Real-time Rt-pcrmentioning
confidence: 99%